2015
DOI: 10.7554/elife.10837
|View full text |Cite
|
Sign up to set email alerts
|

Active contraction of microtubule networks

Abstract: Many cellular processes are driven by cytoskeletal assemblies. It remains unclear how cytoskeletal filaments and motor proteins organize into cellular scale structures and how molecular properties of cytoskeletal components affect the large-scale behaviors of these systems. Here, we investigate the self-organization of stabilized microtubules in Xenopus oocyte extracts and find that they can form macroscopic networks that spontaneously contract. We propose that these contractions are driven by the clustering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
154
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(181 citation statements)
references
References 51 publications
25
154
2
Order By: Relevance
“…The clustering of parallel microtubules into poles presents a geometric problem when forces are indiscriminately applied all along microtubules: inversely oriented motors between parallel microtubules will oppose each other, resulting in gridlock, unless symmetry is broken by dynein enrichment at microtubule minus-ends (Hyman and Karsenti, 1996;McIntosh et al, 1969;Surrey et al, 2001). In computational models, localizing a minus-end-directed motor at microtubule ends permits microtubule clustering into asters or poles (Foster et al, 2015;Goshima et al, 2005;Nedelec and Surrey, 2001;Surrey et al, 2001) and the emergence of a robust steady-state spindle length (Burbank et al, 2007). More recently, experimental work has shown that dynein-dynactin and NuMA do indeed selectively localize to spindle minus-ends, with dynein pulling on them after kinetochore-fiber (k-fiber) ablation in mammalian spindles (Elting et al, 2014;Sikirzhytski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The clustering of parallel microtubules into poles presents a geometric problem when forces are indiscriminately applied all along microtubules: inversely oriented motors between parallel microtubules will oppose each other, resulting in gridlock, unless symmetry is broken by dynein enrichment at microtubule minus-ends (Hyman and Karsenti, 1996;McIntosh et al, 1969;Surrey et al, 2001). In computational models, localizing a minus-end-directed motor at microtubule ends permits microtubule clustering into asters or poles (Foster et al, 2015;Goshima et al, 2005;Nedelec and Surrey, 2001;Surrey et al, 2001) and the emergence of a robust steady-state spindle length (Burbank et al, 2007). More recently, experimental work has shown that dynein-dynactin and NuMA do indeed selectively localize to spindle minus-ends, with dynein pulling on them after kinetochore-fiber (k-fiber) ablation in mammalian spindles (Elting et al, 2014;Sikirzhytski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An intensity image revealed that asters and other large assemblies of microtubules form within minutes of Taxol addition (Figure 3A), as observed previously (Verde et al. , 1991; Foster et al. , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In recent experiments by Foster et al [39] they examined the spontaneous contraction dynamics of radial MT arrays or asters labeled with Alexa647-tagged tubulin, in Xenopus egg extracts. We have taken a time-series of such asters from published data (kindly shared by the author Peter J.…”
Section: Resultsmentioning
confidence: 99%
“… (A) A time-series of MT asters undergoing fusion (time-series taken from previous work by Foster et al [39]) was analyzed using AMTraK. The grey scale bar indicates normalized fluorescence intensity of Alexa-647 labeled tubulin.…”
Section: Resultsmentioning
confidence: 99%